Developing Creative Thinking Skills in EFL Classes in Morocco - Smare, Zaina; Elfatihi, Mohamed (International Journal of Language and Literary Studies, 2022)
The present paper reports on an evaluation study investigating the extent to which Moroccan EFL high school classrooms encourage the development of creative thinking skills. Our objectives were: to explore the extent to which educational policy documents, namely the National Charter for Education and Training (1999), the White Paper (2002) and the Guidelines for teaching English (2007) promote the development of creative thinking; to find out whether Ticket to English 2 textbook has the potential to support students to think creatively; to investigate teachers’ perceptions and attitudes towards developing creative thinking and to discover insights into the nature of classroom environment with regard to the development of the skill. The study used a mixed methods design which involves a mixture of qualitative and quantitative approaches. The purpose behind this choice is to investigate the match between the aims and objectives outlined in educational policy documents and their implementation through the textbook and teaching practices. The study employed five research instruments namely documents analysis, textbook evaluation, questionnaires, classroom observation, and a semi-structured interview. The results revealed that the importance of creative thinking has been emphasized in policy documents, yet the textbook and teaching practices focus on lower-order thinking skills, such as remembering and understanding. The study concludes with practical recommendations for policy makers, textbook designers, teachers, and teacher development programs.